Linger - Stiefvater, Maggie 1981- (New York Scholastic Press, 2010)
As Grace hides the vast depth of her love for Sam from her parents and Sam struggles to release his werewolf past and claim a human future, a new wolf named Cole wins Isabel's heart but his own past threatens to destroy the whole pack
1
Keywords: Human-animal relationships -- Fiction; Love -- Fiction; Metamorphosis -- Fiction; Supernatural -- Fiction; Wolves -- Fiction